2004
DOI: 10.1002/sita.200400034
|View full text |Cite
|
Sign up to set email alerts
|

Proximal B cell receptor signaling pathways

Abstract: Engagement of the B cell antigen receptor by antigen initiates a complex and interconnected cascade of signaling pathways that determine whether a B cell will divide, differentiate, or die. Both biochemical and genetic studies have defined the principal molecules, including the BCR components Igα and Igβ, Src kinases, Syk, and Btk. Linker proteins such as BLNK have recently been shown to play a vital role in organizing proximal signaling molecules and coupling the BCR to distal signaling pathways. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 285 publications
(245 reference statements)
0
13
0
Order By: Relevance
“…[14][15][16] Leukemic B lymphocytes were purified from the peripheral blood of 51 CLL patients, and were analyzed for ERK1/2 and AKT phosphorylation by Western blot. Constitutive phosphorylation of ERK1/2 was observed in 25 (49%) of 51 patients ( Figure 1A top panel) as revealed by densitometric analysis ( Figure 1C) that allowed to clearly distinguish these cases from those who expressed low if any phosphorylation of the protein (26/51 cases, 51%) ( Figure 1A,C).…”
Section: Erk But Not Akt Is Constitutively Phosphorylated In a Propormentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] Leukemic B lymphocytes were purified from the peripheral blood of 51 CLL patients, and were analyzed for ERK1/2 and AKT phosphorylation by Western blot. Constitutive phosphorylation of ERK1/2 was observed in 25 (49%) of 51 patients ( Figure 1A top panel) as revealed by densitometric analysis ( Figure 1C) that allowed to clearly distinguish these cases from those who expressed low if any phosphorylation of the protein (26/51 cases, 51%) ( Figure 1A,C).…”
Section: Erk But Not Akt Is Constitutively Phosphorylated In a Propormentioning
confidence: 99%
“…[14][15][16] Because it has been reported that CLL B cells carry constitutively phosphorylated Syk and contain high Lyn tyrosine kinase activity, 17 which are both upstream from the MAPK pathway, we aimed at determining the activation status of these 2 kinases in the CLL cells from our patients with a different phosphorylation status of MEK/ERK1/2. Consistent with previous observations in CLL, 12 we confirmed that all CLL patients tested showed constitutively phosphorylated Syk and Lyn (6 and 4 cases, respectively, data not shown).…”
Section: Constitutive Activation Of Bcr-proximal Signaling Molecules mentioning
confidence: 99%
See 1 more Smart Citation
“…Upon engagement of the B cell antigen receptor (BCR) 3 by binding polyvalent antigens, immunoreceptor tyrosine-based activation motifs in the cytoplasmic domains of Ig-␣ and Ig-␤ are phosphorylated leading to the recruitment of Syk to the receptor complex and its phosphorylation on tyrosine and subsequent activation (1). Syk is then required for coupling the BCR to the phosphorylation and activation of the downstream regulatory and adaptor molecules BLNK/SLP65, phosphoinositide 3-kinase, Btk, and phospholipase C-␥2, leading to the activation of Akt and protein kinase C, the mobilization of Ca 2ϩ , activation of the Ras/Raf/ERK and p38 mitogen-activated protein kinase (MAPK) signaling cascades, and activation of the transcription factors NF-B and NFAT.…”
mentioning
confidence: 99%
“…Ig-b forms a covalently linked heterodimer with Ig-a (encoded by the mb-1 gene, also known as CD79a), which associates via its membrane domains with the transmembrane region of Ig heavy (IgH) chains to form precursor B cell receptor (pre-BCR) and B cell receptor (BCR) complexes (for review see [1,2]). Signals emanating from these Ig receptors are essential for differentiation, proliferation and survival of B lymphoid cells [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%